\(\sqrt{x^2+1}+\sqrt{3x+5}=\sqrt{x^2+6x+11}\)
Giải phương trình:
a)\(\sqrt{\sqrt{5}-\sqrt{3x}}=\sqrt{8+2\sqrt{15}}\)
b)\(\sqrt{4x-20}-3\sqrt{\dfrac{x-5}{9}}=\sqrt{1-x}\)
c) \(\sqrt{4x+8}+2\sqrt{x+2}-\sqrt{9x+18}=1\)
d) \(\sqrt{x^2-6x+9}+x=11\)
e) \(\sqrt{3x^2-4x+3}=1-2x\)
f) \(\sqrt{16\left(x+1\right)}-\sqrt{9\left(x+1\right)}=4\)
g) \(\sqrt{9x+9}+\sqrt{4x+4}=\sqrt{x+1}\)
f) Ta có: \(\sqrt{16\left(x+1\right)}-\sqrt{9\left(x+1\right)}=4\)
\(\Leftrightarrow4\left|x+1\right|-3\left|x+1\right|=4\)
\(\Leftrightarrow\left|x+1\right|=4\)
\(\Leftrightarrow\left[{}\begin{matrix}x+1=4\\x+1=-4\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-5\end{matrix}\right.\)
g) Ta có: \(\sqrt{9x+9}+\sqrt{4x+4}=\sqrt{x+1}\)
\(\Leftrightarrow5\sqrt{x+1}-\sqrt{x+1}=0\)
\(\Leftrightarrow x+1=0\)
hay x=-1
a) \(\sqrt{4x^2-4x+1}=3\)
b)\(\sqrt{x^2-10x+25}+2-x\)
c)\(\sqrt{x^2-6x+9}+x=11\)
d)\(\sqrt{3x+19}=x+3\)
e)\(\sqrt{x^2+x+5}-1=x\)
a: =>|2x-1|=3
=>2x-1=3 hoặc 2x-1=-3
=>2x=-2 hoặc 2x=4
=>x=2 hoặc x=-1
c: \(\Leftrightarrow\left|x-3\right|=11-x\)
=>x<=11 và (x-3)^2=(11-x)^2
=>x<=11 và x^2-6x+9=x^2-22x+121
=>x<=11 và 16x=112
=>x=7
d:
ĐKXĐ: 3x+19>=0
=>x>=-19/3
PT =>x>=-3 và (3x+19)=(x+3)^2=x^2+6x+9
=>x>=-3 và x^2+6x+9-3x-19=0
=>x>=-3 và (x+5)(x-2)=0
=>x=2
e: =>\(\sqrt{x^2+x+5}=x+1\)
=>x>=-1 và x^2+x+5=x^2+2x+1
=>x>=-1 và 2x+1=x+5
=>x=4
gpt:\(\sqrt{3x^2+6x+4}+\sqrt{2x^2+4x+11}=\left(1-x\right)\left(x+3\right)\)
\(\sqrt{3x^2+6x+7}+\sqrt{5x^2+10x+21}=5-x^2-2x\)
\(\sqrt{x^2-x+2}+\sqrt{x^2-3x+6}=2x\)
Giải phương trình:
1, \(\sqrt{x^2+2x}+\sqrt{2x-1}=\sqrt{3x^2+4x+1}\)
2, \(x^3-3x^2+2\sqrt{\left(x+2\right)^3}-6x=0\)
3, \(2x^3-x^2-3x+1=\sqrt{x^5+x^4+1}\)
4, \(5\sqrt{x^4+8x}=4x^2+8\)
5, \(\left(x^2+4\right)\sqrt{2x+4}=3x^2+6x-4\)
6, \(\left(x^2-6x+11\right)\sqrt{x^2-x+1}=2\left(x^2-4x+7\right)\sqrt{x-2}\)
Giải phương trình bằng phương pháp bất đẳng thức
1, \(\sqrt{x^2-6x+11}+\sqrt{x^2-6x+13}+\sqrt[4]{x^2-4x+5}=3+\sqrt{2}\)
2, \(\sqrt{x-10}+\sqrt{30-x}=x^2-40x+400+2\sqrt{10}\)
3, \(x^2-3x+3,5=\sqrt{\left(x^2-2x+2\right)\left(x^2-4x+5\right)}\)
4, \(\sqrt{5x^3+3x^2+3x-2}=\dfrac{x^2}{2}+3x-\dfrac{1}{2}\)
5, \(2\sqrt{7x^3-11x^2+25x-12}=x^2+6x-1\)
@Nguyễn Huy Thắng@Mysterious Person@bảo nam trần@Lightning Farron@Thiên Thảo@Sky SơnTùng
\(\sqrt{2x+11}+\sqrt{x-1}\) ; \(\dfrac{\sqrt{-5x}}{x}\) ; \(\dfrac{\sqrt{7x^2+1}}{5}\); \(\sqrt{x^2-14x+33}\); \(\dfrac{\sqrt{-x^2+6x+16}}{-2}+\dfrac{x^2-2x}{3x^2}\)
Tìm ĐKXĐ của x để các biểu thức trên có nghĩa
a: ĐKXĐ: \(x\ge1\)
b: ĐKXĐ: \(x< 0\)
c: ĐKXĐ: \(\left[{}\begin{matrix}x\ge11\\x\le3\end{matrix}\right.\)
1) ĐKXĐ: \(\left\{{}\begin{matrix}2x+11\ge0\\x-1\ge0\end{matrix}\right.\)\(\Leftrightarrow x\ge1\)
2) ĐKXĐ: \(\left\{{}\begin{matrix}-5x\ge0\\x\ne0\end{matrix}\right.\)\(\Leftrightarrow x< 0\)
3) ĐKXĐ: \(7x^2+1\ge0\left(đúng\forall x\right)\Leftrightarrow x\in R\)
4) ĐKXĐ: \(x^2-14x+33\ge0\Leftrightarrow\left(x-11\right)\left(x-3\right)\ge0\)
\(\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x-11\ge0\\x-3\ge0\end{matrix}\right.\\\left\{{}\begin{matrix}x-11\le0\\x-3\le0\end{matrix}\right.\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x\ge11\\x\le3\end{matrix}\right.\)
5) ĐKXĐ:
+) \(-x^2+6x+16\ge0\)
\(\Leftrightarrow-\left(x^2-6x+9\right)+25\ge0\)
\(\Leftrightarrow\left(x-3\right)^2\le25\Leftrightarrow-5\le x-3\le5\)
\(\Leftrightarrow-2\le x\le8\)
+) \(3x^2\ne0\Leftrightarrow x\ne0\)
\(\Rightarrow\left\{{}\begin{matrix}-2\le x\le8\\x\ne0\end{matrix}\right.\)
1/
2/
3/
4/
giải phương trình :
a, \(\dfrac{4x-1}{\sqrt{4x-3}}+\dfrac{11-2x}{\sqrt{5-x}}=\dfrac{15}{2}\)
b, \(\left(\sqrt{5x-1}+\sqrt{x-1}\right)\left(3x-1-\sqrt{5x^2-6x+1}\right)=4x\)
tìm ĐKXĐ
1, \(\sqrt{6x+1}\)
2,\(\dfrac{\sqrt{3}-4}{\sqrt{3x-5}}\)
3, \(\sqrt{\dfrac{2\sqrt{15}-\sqrt{59}}{x-7}}\)
4,\(\sqrt{\dfrac{-3x}{1-\sqrt{2}}}\)
5, \(\sqrt{\sqrt{5}-\sqrt{3}x}\)
1.
6x + 1 ≥0
<=>6x≥-1
<=>x≥-1/6
2.
3x - 5 > 0
<=> 3x > 5
<=> x > 5/3
5.
√5 - √3 . x ≥0
<=> √3 . x ≤ √5
<=> x ≤ √5/3 = (√15)/3